2017
DOI: 10.1007/s00439-017-1851-2
|View full text |Cite
|
Sign up to set email alerts
|

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis

Abstract: Human Waardenburg syndrome 2A (WS2A) is a dominant hearing loss (HL) syndrome caused by mutations in the microphthalmia-associated transcription factor (MITF) gene. In mouse models with MITF mutations, WS2A is transmitted in a recessive pattern, which limits the study of hearing loss (HL) pathology. In the current study, we performed ENU (ethylnitrosourea) mutagenesis that resulted in substituting a conserved lysine with a serine (p. L247S) in the DNA-binding domain of the MITF gene to generate a novel miniatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…MITF L247S/L247S confers an eye developmental defect and can be observed as early as embryonic day 28 (E28; Hai et al , ). To further investigate the developmental competency of pig embryos derived from the blastocyst complementation, cloned embryos derived from MITF L247S/L247S male PEFs were used as the host and blastomeres of cloned embryos derived from female LW PEFs were used as donors for complementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MITF L247S/L247S confers an eye developmental defect and can be observed as early as embryonic day 28 (E28; Hai et al , ). To further investigate the developmental competency of pig embryos derived from the blastocyst complementation, cloned embryos derived from MITF L247S/L247S male PEFs were used as the host and blastomeres of cloned embryos derived from female LW PEFs were used as donors for complementation.…”
Section: Resultsmentioning
confidence: 99%
“…The MITF L247S/L247S E44 fetus displayed an anophthalmic phenotype and showed a loss of RPE cells (Steingrimsson et al , ; Hai et al , 2017b; Fig A). The eyes of NW‐2 showed normal morphologically and were similar to those of the wild‐type (WT) fetus (Fig A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waardenburg syndrome (WS) is a rare genetic condition characterized by at least some degree of congenital hearing loss and pigmentation deficiencies [ 1 ]. WS has more than 20 mutations in the Mitf allele [ 2 , 3 ], including Mitf mi-vga9 , Mitf mi-bw , and Mitf mi-ce , which have been identified to cause hearing loss and changes in pigmentation. Although the mouse model is widely used in disease phenotypes and pathogenic mechanisms of deafness-related research [ 4 8 ], many shortcomings have also been found in studying human genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a good deal of research regarding the histology, electrophysiology, and development of the miniature pig inner ear (Guo et al ., , ). In addition, gene expression (Wang et al ., ), gene regulation (Chen et al ., ; Hai et al ., , ), and gene transformation (Ma et al ., ; Shi et al ., ) studies of the auditory system have achieved remarkable results. The miniature pig has even been used to study cochlear implants (Chen et al ., ).…”
mentioning
confidence: 99%